The Relation Between Non-Audit Service Fees and Audit Independence: Evidence from United Kingdom - ZHOU, QINWEN (2017)
The aim of this paper is to identify whether non-audit service (NAS) fees are related with audit independence measured as the tendency for auditors to issue going concern opinions. Using sample in financially distressed companies in U.K. in 2015, it is demonstrated that non-audit service fees are negatively correlated with going concern opinions. This result is consistent with Australian studies Wine (1994) and Shama and Sidhu (2001) that using fee ratio to estimate NAS fees. However, it is opposite with DeFond et al. (2004) and Lim and Tan (2008) who use similar models but U.S. samples. Regarding U.K. studies, it is consistent with Firth (2002) and Basioudis et al. (2008) that the effect of NAS on going concern opinions is negative. However, it is contrary to Lennox (1999) who reported no effect of NAS on going concern opinions. This result suggests that audit markets are different between various countries.